Novel stability-indicating RP-UPLC method for simultaneous estimation of sitagliptin and ertugliflozin in bulk and pharmaceutical formulations - Ramya kuber B; Swetha Addanki (SpringerOpen, 2021)
Abstract Background The present investigation was proposed to develop a simple, sensitive, rapid, accurate, precise stability-indicating RP-UPLC method for simultaneous estimation of sitagliptin and ertugliflozin. Chromatographic separation was performed with Waters Hibar C8 [100×2.1mm, 2μ] column and mobile phase acetonitrile: water (pH 3.5) [50:50%, v/v], pumped at a flow rate 0.2ml/min. The separated analytes were detected with a UV detector at a wavelength of 218nm. Results The separation of sitagliptin and ertugliflozin was done at a retention time of 0.859min and 1.570min, respectively. The present method was validated according to the ICH guidelines Q2 R1, and stability-indicating studies were carried out as per ICH guidelines Q1A R2. Intra-day and inter-day precision were found to be within acceptable limits. The linearity of the proposed method was in the concentration range of 25-125μg/ml and 3.75-22.5μg/ml for sitagliptin and ertugliflozin, respectively. Limit of detection (LOD) and limit of quantification (LOQ) were found to be 0.5μg/ml and 1.53μg/ml for sitagliptin and 0.13μg/ml and 0.38μg/ml for ertugliflozin, respectively. The recovery of the method was found in between 99.7% and 100.7%. Conclusion The proposed method was able to distinguish the analytes from by-products. Hence, the method was successfully implied for stability-indicating studies and for routine examination of sitagliptin and ertugliflozin in pharmaceutical formulation.